Avaliação de acelerantes de incêndio empregando espectrometria de massas com ionização paper-spray e ferramentas quimiométricas - Adriana Rocio Vargas Prieto (2017)
The forensic analysis of fires is very complex since the evidences aredestroyed by the fire itself. The analysis is intended to classify fires asaccidental or intentional. The development of modern technology allows one to use physics and chemistry in this difficult task. Thus, the determination of the presence of an organic solvent in the fire residues allows the formulation of a hypothesis about the nature of the fire (accidental or arson). Historically the basis of this analysis has been the determination of the presence or absence of an ignitable liquid in the fire debris. Throughout the years the analysis of ignitable liquids (IL) in fire debris has changed as the technology and as the forensic sciences advances. The most used technique now a days is gas chromatography coupled to mass spectrometry. This technique is related to a serious of variables that are difficult to control: Finding debris fire keys, collecting and storing the samples in a timely manner, preparing the sample,employ a sensitive analytical technique and interpret the results to differentiate the types of ignition liquid used to cause the fire. Therefore, fire research is complex and involves many variables, requiring a lot of development in the area. In this work, a new analytical technique developed in the last decade known as Paper Spray Ionization Mass Spectrometry (PS-MS) was used, aiming to find applicability of this technique in the analysis of fire residues combining the advantages of the chemometric tools as unsupervised classifications (Principal Component Analysis-PCA) and supervised (Partial least squares discriminant analysis-PLS-DA). Thus, in this work, three formswere evaluated for fuels analysis: liquid samples, evaporated and thoseobtained by means of a fire simulation. Mass spectra of gasoline were obtained ions [M + H] + consistent with ions of nitrogenated molecules. The mass spectra obtained from the samples were complex due to the large number of components and their nature in each of the analyzed ignition liquids. In the chemometry, 49 samples were taken between liquid, evaporated and fire simulations in three materials (concrete, wood and soil). The classification model selected was the supervised model PLS2-DA. To validate the methodology applied in the preparation of the samples and the analytical technique, figures of merit (FOM) were calculated, which allowed to establish as sensitivity and selectivity rate above 85%. The technique and methodology for the extraction of the residual volatile molecules in the traces of fire presentedgreat potential as a low cost alternative in forensic laboratories, however, this is an innovative work and more studies need to be carried out.